Natural language processing for economic and financial modelling - Ahrens, M (2023)
Over the past years, researchers have introduced various natural language processing (NLP) methods to the fields of economics and finance. It is time to take stock and systematically evaluate which NLP methods work best for the most common domain specific tasks, under the most common domain specific data characteristics, and to let those findings guide future research. We underline the importance of evaluating multimodal (text and numeric) data tasks, since many text datasets in economics and finance come accompanied by potentially relevant numeric metadata. Particularly in the field of modern monetary economics, multimodal data analysis is of vital importance. Ever since the global financial crisis, central bank communication has become a key monetary policy tool. The development of multimodal data analysis frameworks is pivotal for modern day monetary policy research, yet the integration of NLP methods into economic and financial modelling processes is far from being conclusively answered.